Reversible and DNA computing - Babu, Hafiz Md. Hasan, 1966- (Hoboken, NJ : John Wiley & Sons, Inc., 2021)
"Energy consumption is an important aspect of most computing systems today and this is especially true for embedded systems and battery-dependent computers. Reversible computing has the potential to reduce power consumption and heat dissipation. Moreover, traditional silicon computers consume much more power as compared to the computing systems based on Reversible Deoxyribonucleic Acid (DNA). "Reversible and DNA Computing" is the first effort to focus on reversible computing for graduate and post-graduate students, individual researchers, academicians, and industry professionals. This book elaborately discusses the reversible concept with appropriate examples which will help students, academicians and all levels of researchers find new dimensions of research in the energy efficient reversible and DNA computing paradigm. The book discusses from fundamentals to advanced levels of reversible circuits, reversible fault tolerant circuits and reversible DNA circuits"--
Includes bibliographical references and index.
Keywords: Molecular computers